STRATEGI GURU DALAM PENANAMAN KEDISIPLINAN PADA KELOMPOK A DI PAUD NURUL ISLAM - Hasanah, Siti; Risna, Inten; Sari, Muthia (Jurnal Anak Bangsa, 2025)
Discipline in the context of early childhood education can be interpreted as a child's ability to follow applicable rules and norms. PAUD Nurul Islam is an educational institution where children's disciplinary abilities are not yet optimal. Some children still experience difficulties in following established rules and routines, such as arriving late to school, throwing rubbish out of place and not heeding teacher instructions. The aim of this research is to determine the disciplinary conditions of group A children at PAUD Nurul Islam Kragilan and to determine the disciplinary strategies used at PAUD Nurul Islam Kragilan. This research uses a qualitative research method with a case study approach. The subjects in this research were Group A children and PAUD teacher Nurul Islam Kragilan. The data collection technique used in this research is interviews. Based on the findings obtained, the cultivation of discipline in early childhood at PAUD Nurul Islam is carried out through various approaches involving teachers as role models. The condition of children's discipline is not based on their conscience but is influenced by other people. Teachers at PAUD Nurul Islam use various strategies to instill discipline in children, one of which is through habituation, advice and giving rewards. Parents must create a good environment, the school continues to collaborate well and researchers can increase insight into teacher strategies.